Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3855/jidc.360
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in developing countries

Abstract: Globally, Cryptosporidium infection continues to be a significant health problem where it is recognized as an important cause of diarrhoea in both immunocompromised and immunocompetent people. In developing countries persistent diarrhoea is the leading cause of death in children younger than five years of age, where it accounts for 30 to 50 percent of those deaths. Encouragingly an increasing number of investigations in developing countries employ molecular tools, significantly improving the quality of epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 77 publications
0
46
1
3
Order By: Relevance
“…These protozoa are global in their distribution and adversely impact on human health in both developed and developing countries [3,4]. Infections are usually transmitted via the faecal-oral route, following direct or indirect contact with infective stages (oocysts or cysts) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These protozoa are global in their distribution and adversely impact on human health in both developed and developing countries [3,4]. Infections are usually transmitted via the faecal-oral route, following direct or indirect contact with infective stages (oocysts or cysts) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This infection is self-limiting in healthy adult individuals, but can be chronic and fatal in immunocompromised patients and children under 5 years of age 2 . Parasite oocysts are resistant to commonly used methods of water treatment, and contaminated drinking and recreational water are major sources of host to host transmission 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Genomic analysis revealed that C. parvum and C. hominis rely on the enzyme inosine 5′-monophosphate dehydrogenase (IMPDH) for the production of guanine nucleotides 2b, 7 (Scheme 1; Cp IMPDH will be used to denote the parasite enzyme, which is identical in C. parvum and C. hominis ) 8 . Remarkably, these parasites appear to have obtained their IMPDH gene from an ε-proteobacterium by lateral gene transfer 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Between 2004 and 2010, 60% of worldwide reported outbreaks of diseases due to waterborne parasitic protozoa were Cryptosporidium induced (Baldursson and Karanis, 2011). Cryptosporidiosis outbreaks are present in both developing and industrialized countries (Chalmers, 2012) and can be lethal for immunocompromised or weak patients (Snelling et al, 2007). The largest outbreak took place in 1993 in Milwaukee (US), where 403,000 persons were affected and more than 100 died (Mac Kenzie et al, 1994).…”
Section: Introductionmentioning
confidence: 99%